Quality and diagnostic performance of coronary computed tomography angiogram (CCTA): A comparison between pre-liver and pre-kidney transplant patients. Issue 143 (October 2021) - Kirkbride, Rachael R.; Larkin, Emily; Tuttle, Mark K.; Nicholson, Michael D.; Jiang, Brian G.; Liubauskas, Rokas; Matos, Jason D.; Gavin, Michael; Litmanovich, Diana E.
Highlights: 45% of patients had a CAC score of ≥400, and 50% of CCTAs had ≥50% stenosis. CCTA in high-risk pre-transplant patients excluded CAD in 50%, halving ICA need. Diagnostic quality CCTA was achieved in 90% of pre-transplant patients. Increased coronary artery calcium score does not affect CCTA quality. Pre-kidney transplant patients have worse heart-rate control and CCTA quality. Abstract: Purpose: Assess and compare the quality and diagnostic performance of CCTA between pre-liver and pre-kidney transplant patients, and gauge impact of CCTA on ICA requirements. Methods: Patients without known coronary artery disease (CAD) were selected for CCTA if considered high-risk or after abnormal stress testing. All pre-liver and pre-kidney CCTAs between March 2018 and August 2020 were retrospectively included. CCTA quality was qualitatively graded as excellent/good/fair/poor, and CAD graded as < or ≥50% stenosis. Heart rate, coronary artery calcium (CAC) scores, and fractional flow reserve CT (FFRCT ) results were collected. CAD stenosis was graded on invasive coronary angiogram (ICA) images, with ≥50% stenosis defined as significant. Results: 162 pre-transplant patients (91 pre-liver, 71 pre-kidney). Pre-kidney patients had poorer CCTA quality (p = 0.04) and higher heart rate (median: 65 bpm vs 60 bpm, p < 0.001). Out of 147 diagnostic CCTAs (pre-liver: 84, pre-kidney: 63), 73 (49.7%) had a ≥50% stenosis (pre-liver: 38 (45.2%), pre-kidney:35 (55.6%)). 12/38 (31.6%) had a significantly reduced FFRCT, and 19/53 (35.8%) had ≥50% stenosis on ICA. Among patients whose CCTA was diagnostic and had ICA, stenosis severity was concordant in 10/23 (43.5%) pre-liver and 10/25 (40%) pre-kidney patients. All discordant cases had stenosis 'over-called' on CCTA. Conclusion: Diagnostic-quality CCTAs in high-risk pre-transplant patients are achievable and can greatly reduce ICA requirements by excluding significant CAD. CCTA quality is poorer in pre-kidney transplant patients compared to pre-liver, possibly due to higher heart rate.